The Students’ Achievement in Teaching and Learning English Through English Texts - Sarifuddin, Muhamad (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
This study is an Analytical study about students’ achievement in teaching and learning English through English texts. The object of this study is the second year students at MA Putra Al Islahuddiny Kediri in academic year 2025/2026. The total number of the population were more than 100 students, so that the writer reduced the population into sample then the writer got 72 students. The object of the study was teaching English through English texts. After being taught, the students then given some test. The result of the test given shown the average score: 6,125. It is conveniently to judge that the students' achievement in learning english through English text is good enough.